The Influence of Net Profit , Cash Flow and Share Prices on Stock Transaction Volume - Mahendra, Nanda; Ali, Hapzi (Dinasti Publisher, 2024)
The Influence of Net Profit , Cash Flow and Stock Price on Stock Transaction Volume is a scientific article in the literature study within the scope of the field of science. The purpose of this article is to build a hypothesis of the influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The research method with the research library comes from e-books and open access e-journals . The results of this article: 1) Net Profit has an effect on Share Transaction Volume ; 2) Cash Flow has an effect on Stock Transaction Volume ; and 3) Share Price has an effect on Share Transaction Volume